Defining the Neural Mechanisms of Probabilistic Reversal Learning Using Event-Related Functional Magnetic Resonance Imaging - Cools, Roshan; Clark, Luke; Owen, Adrian M; Robbins, Trevor W (The Journal of neuroscience, 2002)
Event-related functional magnetic resonance imaging was used to measure blood oxygenation level-dependent responses in 13 young healthy human volunteers during performance of a probabilistic reversal-learning task. The task allowed the separate investigation of the relearning of stimulus-reward associations and the reception of negative feedback. Significant signal change in the right ventrolateral prefrontal cortex was demonstrated on trials when subjects stopped responding to the previously relevant stimulus and shifted responding to the newly relevant stimulus. Significant signal change in the region of the ventral striatum was also observed on such reversal errors, from a region of interest analysis. The ventrolateral prefrontal cortex and ventral striatum were not significantly activated by the other, preceding reversal errors, or when subjects received negative feedback for correct responses. Moreover, the response on the final reversal error, before shifting, was not modulated by the number of preceding reversal errors, indicating that error-related activity does not simply accumulate in this network. The signal change in this ventral frontostriatal circuit is therefore associated with reversal learning and is uncontaminated by negative feedback. Overall, these data concur with findings in rodents and nonhuman primates of reversal-learning deficits after damage to ventral frontostriatal circuitry, and also support recent clinical findings using this task.